Multipurpose trees in livestock-production systems - Kategile, J.A. (Agroforestry Research and Development in Zimbabwe, 1993)
Africa's demand for food and Development means added pressure on natural resources that are already threatened. There is therefore, and urgent need for technical innovations that will raise productivity of livestosk and crops without causing further environmental degradation. But technical innovations need favourable policy environment in which they can be adapted.